Microdata analytics of out-of-pocket and catastrophic health spending in Mexico: an analysis by quantiles - Rodríguez Aguilar, Román (My University, 2022)
Out-of-pocket and catastrophic health spending are key indicators for assessing the financial coverage of a health system. Out-of-pocket spending represents expenditures related to the health care of a household member, while catastrophic spending represents expenditures that constitute more than 30 % of the household’s ability to pay. Measurements in Mexico of out-of-pocket household spending show that it is an item that has not decreased from 2016 to 2018, the out-of-pocket household spending increased by 4 % real representing in 2018, 109 billion of Mexican pesos. Analysis of out-of-pocket spending by quintile shows that average monthly household spending on health is in the range of Q1-$17 to Q5-$1,900 pesos with high dispersion in the data (SD=1,446). The quantile regression shows that there are significant differences between the factors associated to out-of-pocket spending among the quintiles, especially due to the presence of chronic diseases in the household, belonging to the rural environment, the age of the head of the household and the total number of household members. The incidence of catastrophic spending represented 2.19 % [2.18-2.19, N=760,3030] of total households. According to the results of the logistic model, the incidence of catastrophic spending is mainly influenced by households that had hospital spending (OR=20.13) and maternity spending (OR=20.77). Affiliation with a health institution decreases the probability of incurring catastrophic spending (OR=0.93), and when households are segmented by income quintile, the incidence is higher in Q2 and Q4. Mainly affected by spending on hospitalization and maternal care. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Catastrophic health spending; Logistic regression; Out-of-pocket health spending; Quantile regression; Financial coverage; Health systems